2005
DOI: 10.1128/aem.71.1.312-319.2005
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Auxotrophic Mutants of Diploid Industrial Yeast Strains after UV Mutagenesis

Abstract: Auxotrophic mutants of the yeast Saccharomyces cerevisiae are usually isolated in haploid strains because the isolation of recessive mutations in diploids is thought to be difficult due to the presence of two sets of genes. We show here that auxotrophic mutants of diploid industrial sake yeast strains were routinely obtained by a standard mutant selection procedure following UV mutagenesis. We isolated His(-), Met(-), Lys(-), Trp(-), Leu(-), Arg(-), and Ura(-) auxotrophic mutants of five sake strains, Kyokai n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 58 publications
(71 reference statements)
2
43
0
1
Order By: Relevance
“…This result also suggested that K. marxianus DMKU3-1042 is haploid, because there was no 0.8-kb band corresponding to the wild-type allele in the lys1::ScURA3 strain. If it is diploid, two bands, one containing the insert and other the wild type, should have appeared (18). Further, complementation of the lys1 mutant with ScLYS1 was tested.…”
Section: Downloaded Frommentioning
confidence: 99%
“…This result also suggested that K. marxianus DMKU3-1042 is haploid, because there was no 0.8-kb band corresponding to the wild-type allele in the lys1::ScURA3 strain. If it is diploid, two bands, one containing the insert and other the wild type, should have appeared (18). Further, complementation of the lys1 mutant with ScLYS1 was tested.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Unfortunately, because wine yeast strains are usually prototrophic (and auxotrophic mutants are not easily obtained) the use of these markers has been precluded for industrial strains. This view has been challenged by a recent work by Hashimoto et al (2005) that were able to obtain auxotrophic mutants from industrial wine yeast strains by UV mutagenesis, these mutants would greatly facilitate genetic engineering by allowing the use of recessive selectable markers.…”
Section: Requirements For Efficient Genetic Engineering Of Wine Yeastsmentioning
confidence: 96%
“…These frequencies are lower than the previously reported ϳ100% for gene disruption in a haploid strain. While the targeted gene disruption efficiency of the CRISPR-Cas system was indeed affected by the increased ploidy number, 15 to 60% is still a fairly impressive percentage that could significantly reduce the laborious screening process of other marker gene disruption strategies, which require either large-scale screening (frequencies ranged from 10 Ϫ4 to 10 Ϫ3 ) or time-consuming procedures (27,33). In addition, CRISPR-Cas directed gene disruption does not leave a scar or undesirable selection marker in the yeast genome.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the presumed polyploidy of most industrial yeast strains (25,26), regular gene deletion methods, which have been routinely used with laboratory S. cerevisiae strains to generate auxotrophic markers, are not applicable to polyploid S. cerevisiae strains. The target gene deletion efficiencies of the regular method are not high enough to achieve the deletion of multiple alleles and overcome high frequencies of reversion of the mutated allele through homologous recombination with the wild-type allele from extra copies of the genome (27). Recently, transcriptionalactivator-like effector nuclease (TALENs) has been widely adopted as a genome-editing tool that outperforms the traditional methods (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%